Analysis of Work Effectiveness, Productivity and Work Motivation During the Pandemic Period at PT. Dexa Medica - Y Yosephina; A Ambardi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to analyze work effectiveness, productivity, and work motivation during the Covid-19 pandemic at PT Dexa Medica. Researchers used quantitative research methods to analyze simultaneously and partially between the variables studied. The data used is primary data by distributing questionnaires to 100 respondents and by using secondary data in the form of library research. The sampling used was using the Non Probability Sampling technique by not providing equal opportunities for members of the population to be selected as samples. The technique used in this research is purposive sampling technique. From the results of the study, it can be seen that, work effectiveness has an influence on employee performance (Y) at PT. Dexa Medica Tangerang. In the partial test the work effectiveness sig value of 0.036. Then, for the Productivity variable has an influence on performance at PT Dexa Medica Tangerang where there is a sig value of 0.003. Meanwhile, based on the results of the parisal test, it shows that motivation (X3) has no influence on the performance of employees at PT. Dexa Medica Tangerang. In the partial test of Motivation (X3) there is a sig value of 0.844. The results of the hypothesis test prove that work effectiveness (X1), productivity (X2) and motivation (X3) together have a significant effect on performance. This is indicated by the acquisition of simultaneous test results (F), namely the calculated F value of 3.710 and a significance value of 0.014 at a significance level of 5% where 0.014 <0.05. This states that there is a positive and significant effect between the variables of work effectiveness (X1), productivity (X2) and motivation (X3) on performance.